Conception of a Malicious Node Detection System for Tactical Wireless Sensor Networks - Wiesław JABŁOŃSKI (Koncepcja systemu detekcji złośliwych węzłów dla taktycznych bezprzewodowych sieci sensorycznych, 2024)
This article presents the motivation and outlines a concept for mechanisms supporting data packet routing and exchange in tactical wireless sensor networks. The design of these networks maximises the use of solutions from commercial wireless sensor networks (WSNs) and mobile wireless sensor networks (MWSNs). The proposed mechanism focuses on detecting malicious nodes and reducing their impact on the network. Detection data will be collected passively, and analysis will be conducted using dedicated algorithms based on Dempster-Shafer evidence theory to evaluate and interpret the data. The article provides foundational information on the design, operation, and application of WSNs and MWSNs, including factors influencing their reliability and security. The authors emphasise the importance of reliable packet routing and data exchange in WSNs to ensure optimal performance and resilience. Consequently, maintaining high efficiency and reliable routing in MWSNs is essential for their continued advancement in both commercial and military applications. The article primarily addresses the military domain.
Keywords: Taktyczne bezprzewodowe sieci sensoryczne